A sensitive, high-throughput fluorescent method for the determination of lactoperoxidase activities in milk and comparison in human, bovine, goat and camel milk. (1st March 2021) - Zou, Zhengzheng; Bauland, Julien; Hewavitharana, Amitha K.; Al-Shehri, Saad S.; Duley, John A.; Cowley, David M.; Koorts, Pieter; Shaw, Paul N.; Bansal, Nidhi
Highlights: A sensitive microplate fluorescent assay was developed for milk peroxidase activity. Adding excess exogenous thiocyanate enabled milk normalisation and enzyme activation. High assay sensitivity and reproducibility was demonstrated. Lactoperoxidase activities in milk from four species were comprehensively analysed. A hydrogen/oxygen transfer-based mechanism for LPO in the assay system was proposed. Abstract: Lactoperoxidase (LPO) is one of the major antibacterial ingredients in milk and an extensively employed indicator for milk heat treatment. The traditional method for LPO activity measurement using ABTS (2, 2′-azinobis(3-ethylbenzothiazoline-6-sulphonate) cannot achieve high sensitivity and is affected by indigenous milk thiocyanate. A more sensitive microplate fluorescent assay was developed by monitoring generation of red-fluorescent resorufin from LPO catalysed oxidation of Amplex® Red (1-(3, 7-dihydroxyphenoxazin-10-yl)ethanone) in this study. The assay is particularly suitable for milk LPO activity measurement as it eliminates the influences of indigenous milk hydrogen peroxide and thiocyanate. The method limit of detection was 7.1x10 −6 U/mL of LPO in milk and good intra-run and inter-run precision was obtained. The LPO activities ranked as bovine > goat > camel > human in the four types of milk analysed. The high sensitivity and low cost of this assay makes it suitable for LPO activity analyses in both laboratory and commercial scales.